2010
DOI: 10.1111/j.1440-1681.2010.05402.x
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin is associated with lipid metabolic abnormalities in Lyon hypertensive rats

Abstract: 1. Visfatin (also known as nicotinamide phosphoribosyltransferase or Nampt) is a novel adipokine associated with metabolic abnormalities in obesity and diabetes. The aim of the present study was to determine whether visfatin levels in the circulation and visfatin expression in fat tissues are altered in Lyon hypertensive (LH) rats, a hypertensive strain with numerous metabolic abnormalities, and, if so, to explore the possible correlations between blood visfatin levels and the metabolic abnormalities in LH rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
6
1
1
Order By: Relevance
“…1 and 2). Different from previous results was that serum visfatin levels were elevated and associated with lipids abnormalities in LH rats [15], but we did not observe similar results in SHR and SHR-SP in this study. Furthermore, a downward trend of visfatin serum levels was observed in lean hypertensive rats (Fig.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…1 and 2). Different from previous results was that serum visfatin levels were elevated and associated with lipids abnormalities in LH rats [15], but we did not observe similar results in SHR and SHR-SP in this study. Furthermore, a downward trend of visfatin serum levels was observed in lean hypertensive rats (Fig.…”
Section: Discussioncontrasting
confidence: 84%
“…Serum visfatin levels and local visfatin expression were determined by visfatin (C-terminal) enzyme immunoassay (EIA) kit (Phoenix, Belmont, CA, USA) and western blotting analysis, respectively, as described previously [15]. The EIA kit has an intraassay CV% of \5%, an interassay CV% of \12% and a sensitivity of 0.1 ng/ml.…”
Section: Enzyme Immunoassay and Western Blotting Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, we demonstrated that visfatin, a PVAT‐derived growth factor for vascular smooth muscle cells (VSMC), is highly expressed in PVAT compared with subcutaneous and visceral fat 75 . We also provided evidence that visfatin is involved in cardio‐ and cerebrovascular disease 76–79 . Other studies have shown that visfatin induces inducible nitric oxide synthase and elicits sustained activation of extracellular signal‐regulated kinase (ERK) 1/2 signalling with the induction of NF‐κB in VSMC 80 .…”
Section: Adipokines Inflammation and Cardiovascular Diseasementioning
confidence: 73%